Immorality - "Milo, Ronald D." (Princeton, 1984)
This book explores a much-neglected area of moral philosophy--the typology of immorality. Ronald D. Milo questions the adequacy of Aristotle's suggestion that there are two basic types of immorality--wickedness and moral weakness--and argues that we must distinguish between at least six different types of immoral behavior.
Keywords: Immorality